The state of decentralization of the healthcare system and nutrition programs in the Lao People's Democratic Republic: an organizational study - Phonevilay Viphonephom; Sengchanh Kounnavong; Daniel Reinharz (BMC, 2024)
Abstract Background The Lao People's Democratic Republic (Lao PDR), a lower-middle income country, has a higher malnutrition rate than other Southeast Asian countries. The decentralization of healthcare is a determinant of the effectiveness of programs to reduce malnutrition, but no study has focused on this factor in this country. This organizational study explores the state of decentralization of the healthcare system in Lao PDR that underlies the nutrition programs in the country. Methods A qualitative study, which is based on a neo-institutional theory conceptual framework, explored factors related to dominant structure (laws, regulations, resources) and interpretative schemes (dominant ideas and beliefs) that characterize the nutrition services provided in the Lao healthcare system. Twenty-four semistructured interviews were performed with representatives of healthcare institutions involved in nutrition programs at different government levels, external donors and civil society organizations. The interviews were completed with relevant documents. The analysis focused on the convergence of interpretative schemes of the organizations concerned and the coherence between the structure underpinning the nutrition programs and the interpretative schemes. Results Services deployed to reduce malnutrition in the Lao PDR remain largely centralized, despite factors specific to the country that led it to promote decentralization of its services. The convergence of interpretive schemes and the coherence between the observed structure and the interpretative schemes of actors at all governance levels ensure the stability of this state of decentralization, which has persisted for almost 50 years. Conclusion Nutrition programs in the Laos PDR are largely under the responsibility of the central government. The transformations in the healthcare system, notably with the use of new information technologies and the fact that the provinces are populated by a growing number of professionals trained in nutrition in addition to factors that push the system to be decentralized, such as ethnic diversity, the increasing availability of human resources in provinces, and the use of communication technologies, are not strong enough to change the balance of power between governance levels. The deconcentration that characterizes decentralization is therefore likely to continue for the foreseeable future.